National moderating in Chinese journalism education in 2000–2020 - Yang Zhi (Journal of the Belarusian State University. Journalism, 2022)
The matter of article is to follow realisation of the state politic in modern China in relation to mass media activity and journalism education. The aspiration to save humanitarian and social potentiality of informative and communicative spheres is stressed as a basic level of this practice. The essence and practical significance of Marxism in China, notices «Chinese Marxism» and «specified Chinese socialism» are enlightened too.